Juridical Analysis of Sentencing Disparity in Cases of Joint Commission of Rape and Murder by a Minor in Palembang - Welmar Sonia Aprialda da Silva; Jimmy Pello; Orpa G. Manuain (JURNAL HUKUM SEHASEN, 2026)
This study examines sentencing disparity in cases involving joint participation in rape and murder committed by minors in Palembang. Significant differences in sanctions imposed on several minors involved in the same series of serious crimes raise juridical issues concerning the application of the principle of individual criminal responsibility and proportionality within the juvenile justice system. The research addresses two main questions: why sentencing disparity occurs in such cases and how sentencing should be imposed in accordance with prevailing legal principles. The objective is to analyze the causes of disparity and to formulate an appropriate sentencing framework that reflects justice and balances the protection of child offenders with victims’ rights. This research employs a normative juridical method using statutory, case, and conceptual approaches. Primary, secondary, and tertiary legal materials are analyzed qualitatively through legal interpretation and reasoning methods. The findings indicate that sentencing disparity arises from the suboptimal application of individual criminal responsibility in the context of participation. Judicial considerations tend to emphasize age and the position of the principal offender without proportionally linking them to the level of involvement, intent, and actual contribution of each minor. As a result, the sentencing decisions create imbalances that do not fully reflect proportionality, equality before the law, and substantive justice within the juvenile justice system. Therefore, judges should place greater emphasis on analyzing each offender’s individual role and consistently apply the principle of individual criminal responsibility to ensure a fair balance between child protection and justice for victims.